Attitude and awareness of students towards the reference service at the General Reference Section, University of the Philippines Diliman Main Library - Panchadsaram, Madhuram K. 1958- (1988)
The study used the survey method to achieve the objectives. The subject of this study are the students who used the U. P. Diliman Main Library during the second semester 1987-88. The students came from different colleges within and outside the Diliman Campus. To get a fair representation, five percent (769) of the total population (15,382) of the U. P. Diliman campus student population were selected to be the respondents for this study. The 769 was considered as population. Out of 769 questionnaires, 678 were returned answered. This constitutes an 88.7 percent return.
The subjects of this study are predominantly male (59.7 percent), from the College of Social Science and Philosophy. The highest number of females (30.4 percent) came from College of Engineering. The respondents were classified into undergraduate and graduate students. There are more undergraduate student (92.2 percent) than graduate students (7.1) in this study. Almost all the respondents (above 95 percent) have had occasions to use the reference section though the frequency of usage is rare. They also use the General Reference Section mostly for their class assignment. The graduate students are more aware of the references services that are available to them than the undergraduates. The majority of the respondents indicated that they will seek assistance from the reference librarian when the need arises. Both the undergraduate and graduate students rated the General Reference Section as good.
This descriptive study aims to determine the awareness of student's towards reference services that are available to them at the U. P. Diliman Main Library General Reference Section. The objectives of the study are to find out who uses the General Reference Section, the reason for using, their awareness, and attitudes towards reference services that are available to them.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: University of the Philippines (Diliman). -- Library. -- General Reference Section; Academic libraries -- Reference services; Libraries, University and college -- Reference services